2018
DOI: 10.3138/cjhs.2018-0003
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward condom carriers: The role of gender

Abstract: This study assessed personal attitudes and perceptions of societal attitudes toward condom carriers, with a focus on the role of gender. Although prior research suggests that sexually active women in society are looked down upon, there has been little investigation as to whether this view remains pertinent today, and whether this remains the case at the individual—as opposed to societal—level. Participants were female undergraduate students who read vignettes describing either a male or female condom carrier. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…A recent study in AIDS-infested Nairobi revealed that condom usage is frown upon by both Muslim and Catholic church leaders, as an indirect call for sexual promiscuity [ 28 ]. Another study on college students in Canada revealed that female condom carriers are still judged negatively [ 29 ], even by other females, suggesting that condom usage still relies on male’s disposition. A recent study in Jordan about the contraceptions’use, as reported by women, showed that 38.3% did not use any kind of contraception and only 42.3% were using some medically approved method (pills, condoms).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in AIDS-infested Nairobi revealed that condom usage is frown upon by both Muslim and Catholic church leaders, as an indirect call for sexual promiscuity [ 28 ]. Another study on college students in Canada revealed that female condom carriers are still judged negatively [ 29 ], even by other females, suggesting that condom usage still relies on male’s disposition. A recent study in Jordan about the contraceptions’use, as reported by women, showed that 38.3% did not use any kind of contraception and only 42.3% were using some medically approved method (pills, condoms).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, less ability to access and utilize sexual-risk knowledge, advocate for their own sexuality and condom self-efficacy have been related to women who endorse traditional values and lower rates of condom use are reported by these women in comparison to men (Leung & MacDonald, 2018). Furthermore, hostile attitudes toward women in markedly traditional societies make men more likely to resist condom use in heterosexual intercourse (Curtin et al, 2011;Grose et al, 2014;Leung & MacDonald, 2018). (Inglehart et al, 2014).…”
Section: The Role Of Equality and Egalitarian Values At The Individual Levelmentioning
confidence: 99%
“…Product placement literature demonstrates condom placement in neutral pharmacy locations with increased privacy (e.g., near soap or other personal items) rather than aisles with additional embarrassing products may improve purchasing attitudes and reduce embarrassment (Gebhardt et al 2012;Young et al 2017). Various marketing and public health strategies have been implemented to reduce embarrassment and increase condom purchasing (de Visser 2005;Eastman-Mueller et al 2016;Kerr 1990;Ronis and LeBouthillier 2013), specifically self-checkout, vending machines, and mail-order programs; however, gender differences in purchasing persist (Leung and MacDonald 2018;Refinery 29 2017;Sixsmith et al 2006). While 68% of women viewed female condom purchasers as responsible and empowered (Leung and MacDonald 2018;Refinery 29 2017), only 18% had ever purchased a condom and only 3% carried a condom in their purse (Refinery 29 2017; Trojan™ 2018), illustrating inconsistent attitudes and behaviors.…”
Section: Gender and Purchasingmentioning
confidence: 99%
“…Various marketing and public health strategies have been implemented to reduce embarrassment and increase condom purchasing (de Visser 2005;Eastman-Mueller et al 2016;Kerr 1990;Ronis and LeBouthillier 2013), specifically self-checkout, vending machines, and mail-order programs; however, gender differences in purchasing persist (Leung and MacDonald 2018;Refinery 29 2017;Sixsmith et al 2006). While 68% of women viewed female condom purchasers as responsible and empowered (Leung and MacDonald 2018;Refinery 29 2017), only 18% had ever purchased a condom and only 3% carried a condom in their purse (Refinery 29 2017; Trojan™ 2018), illustrating inconsistent attitudes and behaviors. Further, women and men may associate condom purchasing as a male responsibility (Leung and MacDonald 2018;Mantell et al 2011), decreasing actual purchase behavior.…”
Section: Gender and Purchasingmentioning
confidence: 99%
See 1 more Smart Citation